2018
DOI: 10.1186/s40360-018-0245-y
|View full text |Cite
|
Sign up to set email alerts
|

From population to individuals: a new indicator for evaluating the appropriateness of clinical application of antibiotics

Abstract: BackgroundThis study aims to establish a new indicator based on the anatomical therapeutic chemical/defined daily dose (ATC/DDD) system.MethodsUtilization data of antibiotics of inpatients in a university hospital were used to calculate the indicators of use rate (UR), use density (UD), and ratio of use density to use rate (UD/UR). According to the professional characteristics, the recommended values of UD/UR in different departments were established respectively. Crosswise comparison and appropriateness evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…This study reported a (near) fifty percent DDD per 100 bed-days reduction (Table 6). Similarly to other studies, clinical pathways increase the clinical appropriateness of antibiotics [61][62][63] and reduces broad-spectrum antibiotics regimen, accompanied with fewer antibiotic courses [64].…”
Section: Ddd Decreases After Cp Interventionmentioning
confidence: 92%
“…This study reported a (near) fifty percent DDD per 100 bed-days reduction (Table 6). Similarly to other studies, clinical pathways increase the clinical appropriateness of antibiotics [61][62][63] and reduces broad-spectrum antibiotics regimen, accompanied with fewer antibiotic courses [64].…”
Section: Ddd Decreases After Cp Interventionmentioning
confidence: 92%